IMPROVING STUDENTS’ LEARNING OUTCOMES IN NUCLEAR PHYSICS THROUGH THE APPLICATION OF THE PROBLEM BASED LEARNING (PBL) MODEL - Wahyuni, Sri (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
The research conducted was a classroom action research (CAR) carried out in two cycles. Each cycle consisted of planning, implementing, and observing ended by a daily test. The subject of this research was XII class at SMA 10 Pekanbaru with a total of 41 students. The method used was the PBL (Problem Based Learning) model. Before the implementation of learning improvement, an initial test or pre-test was held, where the average score of pre-cycle was 75. This result did not fulfil the minimum mastery criterion (KKM) set by the school of 80. To overcome this problem, the researcher applied the PBL (Problem Based Learning) model to improve student physics learning outcomes. The results showed that the average score of students in the first cycle increased to 80.71 while the second cycle increased to 86.12. There were significant difference of students who fulfill the minimum mastery criterion in each cycle which 16 students in pre cycle (39.02%), 26 students in cycle I (63.41%), then it increased by 41 students (100%) in cycle II. The highest score of cycle I was 86 and cycle II increased to 90. From the findings, it can be concluded that by applying the PBL model can improve the physics learning outcomes of students at XII class of SMA Negeri 10 Pekanbaru.